BIVARIATE POLYNOMIAL INTERPOLATION BASED ON LINE INTEGRALS - Van Khiem, Nguyen; Van Toan, Do (HNUE Journal of Science: Journal of Natural Sciences, 2025)
We study bivariate polynomial interpolation based on line integrals over line segments connecting two points on two fixed straight lines in the plane. We provide a characterization of the sets of segments that uniquely determine the interpolation polynomial. We also construct illustrative examples for specific cases.